Hemophagocytic lymphohistiocytosis (HLH): A heterogeneous spectrum of cytokine-driven immune disorders. Issue 3 (June 2015) - Brisse, Ellen; Wouters, Carine H.; Matthys, Patrick
Highlights: HLH comprises a broad spectrum of disorders that all present with a cytokine storm. Diverse animal models of HLH have enhanced our understanding of this disease. Models of primary HLH appoint a major role for IFN-γ in disease pathogenesis. TNF-α, IL-6, IL-10 and IL-18 are also cytokines of interest in design of treatments. Targeting hyperactive T cells or DCs may represent an alternative therapeutic option. Abstract: Hemophagocytic lymphohistiocytosis (HLH) comprises a group of life-threatening immune disorders classified into primary or secondary HLH. The former is caused by mutations in genes involved in granule-mediated cytotoxicity, the latter occurs in a context of infections, malignancies or autoimmune/autoinflammatory disorders. Both are characterized by systemic inflammation, severe cytokine storms and immune-mediated organ damage. Despite recent advances, the pathogenesis of HLH remains incompletely understood. Animal models resembling different subtypes of HLH are therefore of great value to study this disease and to uncover novel treatment strategies. In this review, all known animal models of HLH will be discussed, highlighting findings on cell types, cytokines and signaling pathways involved in disease pathogenesis and extrapolating therapeutic implications for the human situation.